Analisis Problematika Putusan Tata Usaha Negara Dalam Sengketa Kepegawaian - Muhammad Sabir Rahman; Muhammad Luthfi N.K (KRTHA BHAYANGKARA, 2022)
The study was intended to know the judge's consideration and application of the judge's law on the employment dispute in rulings number: 102/G/2019/PTUN.Mks. The type of research used in this study is a normative-law study that is analyzed by qualitative methods of decryptive analysis. The source of the legal material used, the primary material consists of regulatory rules, official records such as academic texts and meeting tracts of legislation, and judicial decisions of both the state and the Supreme Court, and secondary legal materials are legal that explain the primary legal material of all non-official documents. The publication of the law includes both textual books and scientific writings that deal with scientific objects. The results of the study can be concluded that the panel of judges is so meticulous an aspect of the substance which cannot be overlooked, because of the accused's error in presenting an object in dispute with the intractable and contrary to the general principles of good government in violation of the principles of thoroughness, that the plaintiff's claim for the limitation of the object a quo must be fulfilled. The panel of judges has applied the proper legal basis in the ruling, so the object that the a quo issue has been handed down in judicial terms.